Jokowi’s Sneakers Politics: Personal Branding, Politics of Imaging and Millenial Votes The 2019 Presidential Election - Suseno, Bayu Aji; Utami, Putri Prabu (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
This study aims to determine the use of sneakers as an artifactual communication medium that affects public perception (potential voters), to form millennial political identities to increase the popularity and electability of the incumbent presidential candidate Jokowi in the 2019 Indonesian presidential election campaign. The theoretical basis for personal branding is to determine the politics of imaging as a millennial leader against Jokowi's hypebeast style with sneakers. This study uses a qualitative research method with a phenomenological approach. The research subject focuses on the phenomenon of Jokowi's hypebeast style with sneakers as a personal branding strategy to win votes from millennials. In contrast, the research object is the sneaker product used by Jokowi during the presidential election campaign from 23 September 2018 to 13 April 2019. The results of this study explain that Jokowi's branding strategy of wearing sneakers is redesigning for self-image in introducing a new identity as a millennial leader. Jokowi is hypebeast style considered to break the new presidential dress order by following the fashion trends that are developing in the country. Joko Widodo (Jokowi) is trying to restore public trust by wearing sneaker brands from local and foreign manufacturers, thus placing Jokowi as an old-class politician who appears contemporary (hype) by adapting the style of millenials.